Comment on Jackson and Sonnenschein (2007) “Overcoming Incentive Constraints by Linking Decisions” - Ball, Ian; Jackson, Matthew O.; Kattwinkel, Deniz (Econometrica, 2022)
WE CORRECT A BOUND in the definition of approximate truthfulness used in the body of the paper of Jackson and Sonnenschein (2007). The proof of their main theorem uses a different permutation-based definition, implicitly claiming that the permutation-version implies the bound-based version. We show that this claim holds only if the bound is loosened. The new bound is still strong enough to guarantee that the fraction of lies vanishes as the number of problems grows, so the theorem is correct as stated once the bound is loosened.